GAME-THEORETICAL MODEL APPLICATION’S TO PLANNING AND CONTROLLING OF THE MATERIAL RESOURCES IN MINE INDUSTRY - Kałuski, Jan (International Journal of Computing, 2011)
The game-theoretical approach to the planning and management of materials needed for the mining enterprise is presented. The hierarchical two-person game with non-zero-sum was developed and justified. For the pure strategies of two persons-players (a government and its laws from one side, and a mining enterprise from another side) a game – decision was selected in a form of the Stackelberg optimal strategies. A scenario of the proposed game has been verified on the example of real data from the coal mine.